Pemanfaatan Media Digital dalam Pengembangan Kompetensi Guru PAUD sebagai Kreator Konten Edukasi Anak Usia Dini - Naura Huwaida; Restu Cindy Taqiyananda; Fetty Ernawati; Nimas Ayu Sekar Wengi (Program Studi Pendidikan Islam Anak Usia Dini, 2026)
The development of digital technology has encouraged the use of social media as an interactive and flexible learning medium. In the context of Early Childhood Education, teachers are required not only to teach but also to develop competencies as education content creators who are creative, innovative, and aligne with the characteristics of young learners. This study aims to examine the use of digital media in developin early childhood teachers’ competencies as educational content creators. The study employed library research method with a narratif review design.Data were collected from books, scientific journal articles, and relevant academic online sources published between 2019 and 2025 throught Google Scholar and national journal portals. The data were analyzed using descriptive qualitative analysis techiques. The findings indicate that digital media and social media can be utilized by early childhood teachers as creative,interactive, and engaging learning tools. The development of teachers competencies as educational content creators includes pedagogical, professional, social, and personal competescies. In additional to having a positive impact on motivation and the quality of learning, the use of social media also requires an understanding of digital ethics, digital literacy, and the ability to filter content wisely. The use of digital media can support the development of early childhood teachers’ competencies as innovative and adaptive educational content creators in response to technological advancement. This study emphasizes the role of early childhood teachers as social media-based educational content creators in supporting digital learning for young children.